KELUARGA SADAR GIZI (KADARZI) DALAM MENUJU GIZI BAIK UNTUK SEMUA - Jahari, Abas Basuni (PERSATUAN AHLI GIZI INDONESIA, 2005)
FAMILY NUTRITION AWARENESSTO ACHIEVE BETTER NUTRITIONAL STATUS FOR ALLEffort to improve nutritional status of the people in the last 20 year had been successfully achieved. The prevalence of Protein-Energy Malnutrition (PEM) decreased from 37.5% in 1989 to 27.5% in 2003. The prevalence of Iodine Deficiency Diseases (IDD) decreased from 27.9% in 1990 to 11.10% in 2003. The number of pregnant mothers with anemia and vitamin A deficiency were also decreasing. No sufficient data on other micronutrients status in Indonesia. Nutrition problem in Indonesia in general is still considered as a public health problem. Nutrition program in Indonesia has not been optimally involving nutrition education activities. In addition, the existing potential resources and sociocultural values in the community have not been taken into account in the implementation of nutrition program. Based on these past experiences, the Ministry of Health will focused its nutrition program to achieve Nutrition Awareness of all families (Keluarga Sadar Gizi, KADARZI) in order to reach to the improvement of nutritional status of the people. Nutritionally aware families are the families that able to know and overcome their own nutrition problem or to find aid from others to solve the problem. Following the development in newparadigm of nutrition program to achieve KADARZI, therefore the nutrition research activities should also in part focused on the development of nutrition education tools based on Communicator, Information, Education (CIE) Technics and Sociocultural aspects in the community.Key words: Family Nutrition Awareness (KADARZI), Communication-Information-Education (CIE)